legal aspects, marine cadastral objects, inventory, identification, rights, restrictions, responsibilities, marine cadastre - Adiyasa, Kevin
Pantai Gapura Makassar Hotel was built partly in coastal land of Losari and partly in the territorial waters of Losari. The geographical condition of Pantai Gapura Makassar Hotel building needs to be furtherly examined related to the legal aspects of marine cadastre considering it has not been regulated firmly. Therefore, the purpose of this final project is to provide recommendations regarding the evaluation of national regulation governing the national marine cadastre in Indonesia based on the case study. The methods in this final project is literature-based through inventory and identification of laws in Indonesia related to the rights, restrictions, and responsibilities of marine cadastre application based on marine cadastral object. The results of the analysis of the rights , restrictions and responsibilities related to the marine cadastral object in Hotel Beach Gapura Makassar indicate that the tenure of space above the water until now has not been set explicitly in the legal aspects and also there are some legal vacuum on the application of the cadastral marine studies on the case of this thesis . Thus indicating that the legal framework related to the implementation of marine cadastre in Indonesia is still not sufficient enough to provide legal certainty and not regulated in the specific law governing marine cadastre .